(untitled) (Contemporary Journal of Social Science Review, 2025)
This study attempts to identify artificial intelligence and human relationships such as the social and psychological impact of AI on university student’s behavior. Public and private sector universities were the part of this study This study used a quantitative approach with a sample size of 120 participants. Data were collected through a Google questionnaire form. The validity and reliability of the research instrument were checked by obtaining expert opinions and collecting data from a few students. The data were analyzed using descriptive statistics. The summary of” Social and Psychological Impact of Artificial Intelligence on the Behaviour of University Students: An Explanatory Study” looks at how artificial intelligence (AI) affects social interactions, relationships, and mental health. The research considers both the good and bad effects of using AI in everyday life, especially in communication, emotional support, and social connections. AI tools like virtual helpers, chatbots, and social robots can improve human interactions by offering convenience and tailored experiences. However, they also bring up worries about becoming too dependent on them, feeling less connected emotionally, and losing real human connections. The study also highlights that using AI in communication can change how people think about each other, possibly lead to loneliness, and affect social interactions. It stresses the importance of thinking carefully about AI’s place in human relationships and suggests using AI in a balanced and ethical way to support, not replace real human connections.